(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This article properly discovers the role of machine learning in the prediction and treatment of cancer. It compares various types of tools of machine learning. The comparison is done on the basis of effectiveness, accuracy, as well as ease of use. The findings that are gathered indicate that the advanced tools help in the process of enhancing the accuracy of the prediction as well as the outcomes of the treatment. These tools include deep learning and ensemble methods. On the other hand, this respective analysis also highlights the importance of these specific tools in the matter of improving personalised medicines. Future research on this respective topic should be focused on the matter of overcoming technical difficulties. It can also keep the focus on implementing machine learning with emerging technologies for achieving better results in cancer treatment.